Sekilas tentang Konsepsi Kenegaraan dalam Pandangan Ali Hasjmy - Nuraini A. Manan (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
li Hasjmy viewed that Pancasila’s tenets are inherent and in accordance with a state foundation that are required by Islam. However, regarding state’s constitution he consistently argued that Qur’an is the only one that serves the basic foundation orconstitution of state. Means that Qur’an must be the main guide for all Muslims whether it is for their personal life or for communal life within a state. It could be said that he does not tolerate the separation between religion and state. All state’s regulation and constitution have to be referred to Qur’an and Prophet’s Tradition, although a state does not proclaim itself as an Islamic State. Here, the main key relies on the implementation ofQur’an’s tenets and Prophet’s Tradition. when both principles are implemented, a state will be automatically called as an Islamic State.